1994
DOI: 10.1089/hwm.1994.11.371
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Chemical Properties of MSWI Bottom Ash with Respect to the Glassy Constituents

Abstract: MSWI bottom ash consists predominantly of x-ray amorphous, glassy constituents. A thorough characterization of the glassy constituents could provide insight into both long term leaching and suitability for technological applications of MSWI bottom ash. In this study the bottom ash glasses were examined using conventional and advanced microanalytical techniques. The glass content of the bottom ash sample used in this study was estimated at 75% (w/w). Although the identity of all crystalline phases was very diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…The major elements found in MSWI BA fractions were Si, Ca, Fe, Na, S, and Mg, which is in accordance with mineralogical data Table 1 Main mineral phases in the composition of 6 combined particle size fractions of MSWI BA. (Section 3.2) and literature (Zevenbergen et al, 1994). Fig.…”
Section: Total Elemental Composition Of Mswi Ba Fractionsmentioning
confidence: 95%
“…The major elements found in MSWI BA fractions were Si, Ca, Fe, Na, S, and Mg, which is in accordance with mineralogical data Table 1 Main mineral phases in the composition of 6 combined particle size fractions of MSWI BA. (Section 3.2) and literature (Zevenbergen et al, 1994). Fig.…”
Section: Total Elemental Composition Of Mswi Ba Fractionsmentioning
confidence: 95%
“…Mercury, for example, tends to be undetectable in Indian FAs, but present in measurable concentrations in FAs from Europe, North America and Australia. Generally, the glass phase and the magnetic fractions in combustion residues contain most of the potentially toxic elements (Zevenbergen et al, 1994;Kukier et al, 2003). Trace metals and salts in fly ash may adversely affect plant colonisation and growth, soil microbial activity, and nutrient balance in plants (Wong and Wong, 1986;Pichtel and Hayes, 1990).…”
Section: Environmental Concerns and Remediationmentioning
confidence: 99%
“…This increase in the residual fraction may indicate that the element was occluded in secondary minerals during incineration. Likewise, Zevenbergen et al (1994) indicated that most PTE exist as a solid solution in combustion residues. Between 14.7% and 21.9% of Zn was recovered as OM-Zn in SS or AS, a higher percentage than other studies (Amir et al, 2005;Obrador et al, 2001), whereas relatively low amounts of Zn were found in the water-soluble and exchangeable fraction.…”
Section: Article In Pressmentioning
confidence: 99%